The Ability to Understand Concepts: Cognitive Style, Cognitive Structure, Learning Styles and Learning Motivation - Suharto Suharto; Wahyu Widada; Agus Susanta; Saleh Haji (University of Bengkulu, 2021)
Mathematics is a compulsory subject in vocational high schools throughout Indonesia. The ability to understand concepts is a competency that must be possessed in mathematics learning. The purpose of this study was to examine the variables that affect the ability to understand mathematical concepts. The variables are cognitive style, cognitive structure, learning style and learning motivation. This is a survey research, with a sample of 100 people. The sample was selected by simple random technique from all vocational high school students in Bengkulu City. The research instrument consisted of five instruments, namely a test of the ability to understand mathematical concepts, and four questionnaires of cognitive style, cognitive structure, learning styles and learning motivation questionnaire. The research data were analyzed through path analysis using SPSS and the Lisrel Application Program. The results of this study are the variables of cognitive style, cognitive structure, learning style, and learning motivation have a positive direct effect on the ability to understand mathematical concepts. From this study it can be concluded that the ability to understand mathematical concepts through cognitive styles, cognitive structures, learning styles, and student learning motivation is in a good category.